To simplify the expression \( \frac{8}{8^{2/3}} \), we can start by rewriting the numerator and denominator with the same base.
Recall that: \[ 8 = 8^{1} \]
So we can rewrite the expression as follows: \[ \frac{8^{1}}{8^{2/3}} \]
When we divide powers with the same base, we subtract the exponents: \[ 8^{1 - \frac{2}{3}} = 8^{\frac{3}{3} - \frac{2}{3}} = 8^{\frac{1}{3}} \]
Now, \( 8^{\frac{1}{3}} \) is the cube root of 8, which is: \[ \sqrt[3]{8} = 2 \]
Thus, the simplified expression is: \[ \boxed{2} \]